Chicha, A refreshing Peruvian tradition - Fernández Díaz, Edulgerio (2015)
Lambayeque is a blessed region. It has diverse surrounding villages and impressive cultural richness reflected in this different custom and tradition. Eten and Monsefú are two villages, which have lot of gastronomic secrets. Only the earliest settlers enjoy and know with all those who visit. Chicha is a representative beverage in this region, consumed by currents and ancients Moches. This beverage has many secrets that only their growers secretly know their benefits and mysteries. The aim is to know and decipher riches of these two districts. We have established a dialogue with some people, especially senior citizens who have been able to reveal certain culinary riches of Chicha. Our work made use of the ethnographic research methodology, using several semi structured interviews and field journal. It pretends rescue that ancient knowledge about this beverage, which is helping to preserve and promote cultural, anthropological and richness medicinal of Chicha.